Research on the maker learning experiences of engineering college students majoring in mechanical engineering in China - Wudi Yang; Peng Chen (Scientific Reports)
Abstract Under the background of the construction of new engineering courses, universities have reformed traditional engineering learning models with the concept of maker education, breeding a new model of maker learning. Using the I-E-O model as the analytical framework, and drawing on the seven principles of good practice in undergraduate education, a questionnaire was designed to investigate the entrepreneurial learning experience of engineering college students. Taking mechanical majors as an example, a survey of engineering college students’ maker learning experience was conducted. The study found that first, college students’ commitment to maker learning was high and their satisfaction was good. Second, college students’ comprehensive ability development, maker learning satisfaction, and maker academic participation, maker learning environment were positively correlated. Third, college students’ comprehensive ability development was positively correlated with their perceived maker learning satisfaction. To create meaningful maker learning experiences for engineering students, universities should systematically build a maker learning practice system, governance system, and guarantee system to promote, standardize, and support engineering students in carrying out maker learning activities.